The Influence of Internal Control, Financial Literacy, and Organizational Culture on Financial Performance at LPD in Kintamani District - Kadek Sutawan; Mertyani Sari Dewi; Komang Trisna Sari Dewi (ProBisnis : Jurnal Manajemen, 2023)
This study aims to determine the impact of internal control, financial literacy, and organizational culture on financial performance in LPD Kintamani District. This study uses a quantitative approach. The data collection technique used in this study was in the form of a questionnaire given to the heads of LPDs in the Kintamani District. The data analysis technique used was SEM-PLS (Smart Equation Modeling- Partial Least Square) version 3.0 where the number of samples used in this study were 34 heads of LPD, determining respondents using a purposive sampling technique. The results of the study show that Internal Control has a significant positive effect on Financial Performance in the LPD in Kintamani District. Then Financial Literacy has a significant positive effect on Financial Performance at LPD in Kintamani District. Furthermore,